Measuring urban traffic congestion on the effect of a newly developed commercial area at Taman Tas - Tan, Woei Liang (2017)
Along with the development of a city, transportation issue is always been forgotten and not being taken seriously. The newly developed commercial area at Taman Tas, Kuantan had attracted new traffic trips to/from this area. Serious traffic congestion during peak hours can be seen when high number of trips generated from the newly developed commercial area are combine with the existing through traffic at Jalan Kuantan – Gambang. This study will analyse the level of congestion on a section of Jalan Kuantan-Gambang that stretch along existing and newly developed area at Taman Tas. In this research, the traffic situation is investigated by conducting the questionnaires survey followed by traffic operational analysis using Malaysia Highway Capacity Manual. Finally, the newly suggested level of service of this road section is forecasted using Aimsun TSS software. The result shows the newly developed area at Taman Tas had bring the Level of Service of that section of road to LOS F. By means of some adjustments made and forecasted using Aimsun, the Level of Service is able to be brought up to LOS E.